Anterior cruciate ligament injury rate in young soccer athletes: A systematic review - Api, Gustavo (2023)
OBJECTIVE: To identify the rate of ACL injuries in young soccer athletes.METHODS: The methodology accounted with a systematic search of articles in 4 databases: “Pubmed/Medline”, “Science Direct”, “Web of Science” e “Lilacs”, through the following combined descriptors: “Anterior Cruciate Ligament”, “Injury”, “Adolescents”, “Soccer Players” and “Athletes”. Were selected to the review studies from 2016 to 2021 with data referred to ACL injury in athletes with age from 13 to 18 years old from both sexes. The review followed the PRISMA guidelines and methodological quality assessment performed by STROBE checklist. RESULTS: As a result, 544 studies were found, and those published from 2016 to 2021 were selected (144). Through the steps of reading the titles (89), abstracts (66), and full articles (13), 4 studies were selected that met the inclusion criteria presenting an outcome on the injury rate, where was found a higher incidence of ACL injuries for girls. Despite this, only two of the studies specifically investigated the incidence in relation to other characteristics (activity, mechanism, event).CONCLUSION: It was concluded that the rate of ACL injuries is significantly higher in girls than in boys during adolescence, having characteristics of non-contact injuries and occurring mainly in competitions, but data on the nature of these injuries are still scarce.